2004
DOI: 10.1037/0096-1523.30.3.583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Familiarity on the Perceptual Integrality of the Identity and Expression of Faces: The Parallel-Route Hypothesis Revisited.

Abstract: The effects of familiarity on selective attention for the identity and expression of faces were tested using Garner's speeded-classification task. In 2 experiments, participants classified expression (or identity) of familiar and unfamiliar faces while the irrelevant dimension of identity (or expression) was either held constant (baseline condition) or varied randomly (filtering condition). Selective attention was measured by the difference in performance between these 2 conditions. Failure of selective attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
175
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(195 citation statements)
references
References 65 publications
17
175
2
1
Order By: Relevance
“…We have demonstrated in the current study that identity-dependent expression aftereffects are not the result of local adaptation to image elements of the faces. The existence of an identity-dependent neural representations of expression is also consistent with a number of previous studies (Baudouin, Martin, Tiberghien, Verlut, & Franck, 2002;Ganel, Goshen-Gottstein, & Ganel, 2004;Schweinberger, Burton, & Kelly, 1999;Schweinberger & Soukup, 1998). For example, a recent study of neural responses in monkeys demonstrated that the responses of cells in the amygdala to facial expression depended upon the identity of the monkey demonstrating that expression (Kuraoka & Nakamura, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…We have demonstrated in the current study that identity-dependent expression aftereffects are not the result of local adaptation to image elements of the faces. The existence of an identity-dependent neural representations of expression is also consistent with a number of previous studies (Baudouin, Martin, Tiberghien, Verlut, & Franck, 2002;Ganel, Goshen-Gottstein, & Ganel, 2004;Schweinberger, Burton, & Kelly, 1999;Schweinberger & Soukup, 1998). For example, a recent study of neural responses in monkeys demonstrated that the responses of cells in the amygdala to facial expression depended upon the identity of the monkey demonstrating that expression (Kuraoka & Nakamura, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…Second, in the present study the effect of differences in the discriminability of identity and emotional expression was controlled. The effects of discriminability on the processing of identity and emotional expression has previously been demonstrated in studies of Garner interference (Ganel & Goshen-Gottstein, 2004;Melara, Rao, & Tong, 2002). For instance, Ganel and GoshenGottshtein showed that when the discriminability of identity and expression judgments were equated, Garner interference occurred in both directions.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting data have been reported by Ganel and Goshen-Gottstein (2004), who have explored face processing using the Garner task, which tests for interference effect from one stimulus property on responses to another. Participants categorized photographs according to personal identity information or to emotional expressions, and the effects of variation along the other dimension were explored.…”
mentioning
confidence: 99%
See 2 more Smart Citations